Regulatory regions of SERPINC1 gene: Identification of the first mutation associated with antithrombin deficiency - de la Morena-Barrio, María Eugenia; Antón, Ana Isabel; Martínez-Martínez, Irene; Padilla, José; Miñano, Antonia; Navarro-Fernández, José; Águila, Sonia; López, María Fernanda; Fontcuberta, Jordi; Vicente, Vicente; Corral, Javier (Thrombosis and Haemostasis, 2012)
Antithrombin is the main endogenous anticoagulant. Impaired function or deficiency of this molecule significantly increases the risk of thrombosis. We studied the genetic variability of SERPINC1, the gene encoding antithrombin, to identify mutations affecting regulatory regions with functional effect on its levels. We sequenced 15,375 bp of this gene, including the potential promoter region, in three groups of subjects: five healthy subjects with antithrombin levels in the lowest (75%) and highest (115%) ranges of our population, 14 patients with venous thrombosis and a moderate antithrombin deficiency as the single thrombophilic defect, and two families with type I antithrombin deficiency who had neither mutations affecting exons or flanking regions, nor gross gene deletions. Our study confirmed the low genetic variability of SERPINC1, particularly in the coding region, and its minor influence in the heterogeneity of antithrombin levels. Interestingly, in one family, we identified a g.2143 C>G transversion, located 170 bp upstream from the translation initiation codon. This mutation affected one of the four regions located in the minimal promoter that have potential regulatory activity according to previous DNase footprinting protection assays. Genotype-phenotype analysis in the affected family and reporter analysis in different hepatic cell lines demonstrated that this mutation significantly impaired, although it did not abolish, the downstream transcription. Therefore, this is the first mutation affecting a regulatory region of the SERPINC1 gene associated with antithrombin deficiency. Our results strongly sustain the inclusion of the promoter region of SERPINC1 in the molecular analysis of patients with antithrombin deficiency.
Keywords: SERPINC1; antithrombin; promoter; polymorphisms; thrombosis